Self-Compassion as an Innovative Approach to Maintaining the Mental Well-Being of Adolescents Living in Dormitory - Ginting, Elisa Br; Lumbanbatu, Johannes Sohorimon; Simarmata, Petrus (Kuras Institute, 2024)
Teenagers should seek parental assistance because adolescence is a time of transition from childhood to adulthood and is frequently characterized by the emergence of issues. However, for teenagers living in dormitories, things are different. For this reason, self-compassion is crucial when addressing the mental health issues of young people living in dormitories. The purpose of this study is to examine how self-compassion affects the mental health of adolescents who live in dormitories. This study's methodology blends qualitative and quantitative methods, with 43 participants between the ages of 12 and 18. The Kabanjahe Dormitory in the Karo Regency of North Sumatra served as the site of this study. Research data was gathered through the distribution of questionnaires, in-depth interviews, and observational studies. Multiple linear regression is used in quantitative data analysis, while reduction, presentation, and conclusion-making are the processes used in qualitative data analysis. The study's findings indicate that teens living in dorms have a 21.9% better mental health when they practice self-compassion. Other factors such as parental style, environment, degree of self-disclosure, and education impact the remaining 78.1%. Adolescents living in dorms may be susceptible to mental health issues due to various factors, including exposure to pornographic media, a family history of domestic violence, and inadequate parenting.